(untitled) (International Journal of Food and Nutritional Sciences, 2022)
One of the most important factors affecting dairy firms’ productivity and overall performance is employee engagement. This research looks at the link between productivity and employee engagement in the dairy industry, focusing on a number of factors such motivation, organizational commitment, and work satisfaction. This study uses a mixed-methods approach to discover important determinants of engagement and their effects on productivity indicators. It does this by surveying and interviewing employees of certain dairy firms.